Macro Socio-Economic Factors that Affect the Happiness Index in Indonesia - Pardomuan Robinson Sihombing (SOSHUM : Jurnal Sosial dan Humaniora, 2022)
This study aims to determine the macro socio-economic factors that affect the Happiness Index in Indonesia. The data used comes from the publications of BPS-Statistics Indonesia. The data used is panel data with a research period of 2014, 2017, and 2021 according to the publication time of the Happiness Index. The analysis model used is panel data regression analysis. Of the three panel models tested Common, Fixed, and Random), the fixed effects model was the best. The classical assumption test was carried out on the selected model. The result was that there were violations of the heteroscedastic and autocorrelation assumptions. Because it violates assumptions, the selected fixed effect model is transformed into the white cross-section GLS model. The results obtained, Simultaneously, all independent variables can influence the happiness index with a coefficient of 95 percent. The Gini ratio, the poor, and the open unemployment rate have a significant negative effect on the poverty index. In contrast, HDI, per capita/month expenditure, and economic growth positively impact happiness index. A comprehensive policy is needed so that the level of happiness of the Indonesian people continues to increase.